2003
DOI: 10.1597/1545-1569_2003_040_0449_protsa_2.0.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report of Two-Stage Secondary Alveolar Bone Grafting for Patients with Bilateral Cleft Lip and Palate

Abstract: Objective To overcome the difficulties of one-stage secondary alveolar bone grafting for patients with bilateral cleft lip and palate (BCLP) who have a broad alveolar cleft, the value of two-stage alveolar bone grafting was examined. Patients Three patients (2 girls and 1 boy) with BCLP were treated by two-stage alveolar bone grafting. The procedure consisted of a first-stage surgery (mean age 8 year 6 months ± 7.8 months), which consisted of alveolar bone grafting for one side of the BCLP, and second-stage su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Alternatively, the ABG may be performed unilaterally, with the contralateral ABG being performed several months later. Kamakura et al (2003) report that this may be useful if there is insufficient bone for a single stage procedure, or if there are large alveolar and oronasal fistulae. Two-stage procedures have the disadvantage of undertaking two operations and potentially two donor sites for the bone graft harvest.…”
mentioning
confidence: 99%
“…Alternatively, the ABG may be performed unilaterally, with the contralateral ABG being performed several months later. Kamakura et al (2003) report that this may be useful if there is insufficient bone for a single stage procedure, or if there are large alveolar and oronasal fistulae. Two-stage procedures have the disadvantage of undertaking two operations and potentially two donor sites for the bone graft harvest.…”
mentioning
confidence: 99%
“…Delayed bone healing and a decreased marginal bone level were observed in patients with bilateral clefts compared with unilateral cleft patients because there is less soft tissue for coverage (Sindet-Pedersen et al, 1985). Therefore, we performed two-stage alveolar bone grafting to reduce the strain placed on the soft tissue by the operation and to secure a sufficient blood supply for the covering soft tissue (Kamakura et al, 2003). In addition, the functional stress placed on the grafted bone exerts a strong influence on the volume of the grafted bone, and progressive bone resorption is prevented by movement of the teeth adjacent to the grafted area in the direction of the graft (Bergland et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Kamakura et al (9) has reported a successful 2 stage secondary alveolar bone grafting in bilateral cleft alveolus. The ABG was done one side at a time.…”
Section: Discussionmentioning
confidence: 99%